Hemophilia : Recent Advances - Abrol, Pankaj; Abrol, Pankaj (IntechOpen, 2019)
The book Hemophilia - Recent Advances covers various rapid advances being made in this field. The authors have produced state-of-the art chapters. Over some decades, management of hemophilia has progressed from episode based to prophylaxis. It has moved from plasma and cryoprecipitate to new generations of recombinant coagulation factors. Efforts have been made to cover recent advances in the field. The intricacies of genotype and phenotype of hemophilia are explained. Management with recombinant factors has added to problems like inhibitors, which require more skillful handling. Perioperative management of hemophilia is also explained. Every chapter of this book is peer reviewed and evidence based. The information provided in this book makes the readers well informed and more inquisitive, thereby raising new issues, innovation, and research.
English
Keywords: Haematology; Haematology